Calcium intake and cows' milk free diets. Issue 8 (August 1989) - Devlin, J; Stanton, R H; David, T J
Abstract : In children with atopic eczema on elimination diets, the calcium intake was below the estimated requirement in 15 out of 20 who avoided cows' milk and received no milk substitute, and in three out of 26 who avoided cows' milk but were provided with a soya or casein hydrolysate formula.